The Effect of Financial Management on the Learning Ability of Students in Government-Aided Primary Schools in Ibanda Municipality Uganda - Katureebe, Yazid; Turyamureeba, Silaji; Rahim, Abdul; Eze, Chidinma Esther; Eze, Val Hyginus Udoka (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2023)
This review explores the crucial nexus between financial management and the learning environment within government-aided primary schools in Ibanda Municipality, Uganda. Education in developing nations heavily depends on the efficient allocation and utilization of funds, directly impacting the quality of education and overall learning experience for students. Drawing upon a comprehensive analysis of selected schools in Ibanda Municipality, this review investigates the diverse financial management strategies employed and their subsequent influence on essential educational components, including infrastructure, teaching resources, and student welfare. This review research revealed that there is a direct correlation between effective financial management and the overall enhancement of the learning environment. Schools with robust financial planning mechanisms demonstrate improved infrastructure, better teacher-student ratios, and enhanced availability of educational resources whereas those schools facing financial constraints struggle to survive financially which affects the quality of education. Moreover, this review sheds light on the challenges faced by schools in resource allocation and highlights potential solutions to enhance financial sustainability. It emphasizes the need for strategic financial planning, transparent budgeting, and community involvement to ensure the effective utilization of limited resources.